Redox and anti-oxidant state within cattle oocytes following in vitro maturation with bone morphogenic protein 15 and follicle stimulating hormone - Sutton Mcdowall, Melanie L. (2015)
The developmental competence of cumulus oocyte complexes (COCs) can be increased during in vitro oocyte maturation with the addition of exogenous oocyte-secreted factors, such as bone morphogenetic protein 15 (BMP15), in combination with hormones. FSH and BMP15, for example, induce different metabolic profiles within COCs—namely, FSH increases glycolysis while BMP15 stimulates FAD and NAD(P)H accumulation within oocytes, without changing the redox ratio. The aim of this study was to investigate if this BMP15-induced NAD(P)H increase was due to de novo NADPH production. Cattle COCs were cultured with FSH and/or recombinant human BMP15, resulting in a significant decrease in glucose-6-phosphate dehydrogenase activity (P < 0.05). Inhibition of isocitrate dehydrogenase (IDH) during this process decreased NAD(P)H intensity threefold in BMP15-treated oocytes, suggesting that BMP15 stimulates IDH and NADPH production via the tricarboxylic acid cycle. As NADPH is a reducing agent, reduced glutathione (GSH), H2O2, and mitochondrial activity were also measured to assess the general redox status of the oocyte. FSH alone decreased GSH levels whereas the combination of BMP15 and FSH sustained higher levels. Expression of genes encoding glutathione-reducing enzymes were also lower in oocytes cultured in the presence of FSH alone. BMP15 supplementation further promoted mitochondrial localization patterns that are consistent with enhanced developmental competence. Metabolomics revealed significant consumption of glutamine and production of alanine by COCs matured with both FSH and BMP15 compared to the control (P < 0.05). Hence, BMP15 supplementation differentially modulates reductive metabolism and mitochondrial localization within the oocyte. In comparison, FSH-stimulation alone decreases the oocytes’ ability to regulate cellular stress, and therefore utilizes other mechanisms to improve developmental competence.